SAT0478 Rapid3 questionnaire has high discriminating ability in minimal disease activity attainment in patients with early psoriatic arthritis treated according to tight control strategy in daily clinical practice (results of one-year open-label remarca study). (15th June 2017) - Korotaeva, T; Loginova, E; Koltakova, A; Denisov, L; Chamurlieva, M; Karateev, D; Nasonov, E
Abstract : Background: RAPID3 is an instrument based on patient's report outcomes (PROs) for the assessment of remission and disease activity in rheumatoid arthritis. The advantages of this questionnaire in treat-to-target (T2T) strategy in early psoriatic arthritis (EPsA) have not been studied properly. Objectives: to study discriminating ability of RAPID3 in minimal disease activity (MDA) attainment in patients with EPsA treated during one year according to tight control strategy. Methods: 61 (M/F–29/32) patients (pts) with active EPsA, according to CASPAR criteria, mean age 37±10.6 years, PsA duration 11.3±10.2 months, psoriasis duration 75.4±80.9 months were included. All pts signed a consent form for participation in the open-label REMARCA study. At baseline and after 1year (yr.) of therapy all pts underwent evaluation of PsA activity by Tender Joint count (TJC78), Swollen Joint Count (SJC76), physician's global disease activity (PhGA) VAS, DAS, CRP (mg/l) and by PROs - patient pain global assessment VAS, Patient global disease activity (PGA) VAS, Health Assessment Questionnaire (HAQ) and RAPID3. The dose of Methotrexate (MTX) subcutaneous (s/c) was escalated by 5 mg every 2 weeks from 10 mg/wk up to 20–25 mg/wk. If pts did not achieve MDA after 3–6 months of MTX mono-therapy, combination therapy (CoT) of MTX+Adalimumab (ADA) was started in a standard regime; CoT was continued up to 1 yr. The proportion of pts who achieved MDA was calculated. M±SD, Me [Q25;Q75], %, Spearman rank correlation R, W-test, U-test, ROC-curve analysis were performed. All p<0.05 were considered to indicate statistical significance. Results: By 1 yr. of therapy 36 out of 61 pts (59%) and 25 out of 61 pts (41%) were treated with MTX and with MTX+ADA accordingly. Significant improvements in PsA activity and PROs from baseline up to 1 yr. were observed: DAS 3.93 [3.20–4.58]/1.36 [0.82–2.25], SJC 7 [5–11]/1 [0–3], TJC 8 [6–1]/1 [0–3], PhGA 56 [48–69]/10 [5–20] and VAS pain 54 [48–68]/11 [1–20], PGA 55 [49–68]/14 [7–24], HAQ 0.75 [0.50–1]/0 [0–0.63] accordingly (for all W-test p<0.001). Significant positive correlations between RAPID3 and PsA activity, PROs and CRP are shown in table 1 (for all R p<0.001). MDA was seen in 43 out of 61% pts (70.5%). At the same time RAPID3 and CRP significantly decreased from 12.7 [9.2–16.8] to 4.3 [2.0–7.8] and from 16.6 [8.6–34.6] to 2.1 [0.9–6.7] mg/l accordingly (for all W-test, p<0.001). Among those who have achieved MDA RAPID3 was in "near remission" status and significantly less compared to pts that did not achieve MDA-2.5 [1.3–5.3] and 8.1 [6.0–15.1] accordingly (U-test, p<0.001). According to the results of ROC-curve analysis RAPID3 score had a high discriminating ability for the presence of MDA - AUC 0.888 [0.808–0.969] (Fig. 1 ). Conclusions: RAPID3 based on PROs is a simple instrument for evaluating PsA activity. RAPID3 has shown high discriminating ability in MDA attainment in EPsA pts treated according to tight-control strategy, and could be useful in daily clinical practice. Disclosure of Interest: None declared